Effects of different-intensity exercise and creatine supplementation on mitochondrial biogenesis and redox status in mice - Seyhan Taskin; Hakim Celik; Seniz Demiryurek; Sibel Turedi; Abdullah Taskin (Iranian Journal of Basic Medical Sciences, 2022)
Objective(s): Dietary supplementation combined with exercise may potentiate the beneficial effects of exercise by reducing exercise-induced oxidative stress and improving mitochondrial quality and capacity. In this study, the effects of creatine monohydrate (CrM) supplementation with low and high-intensity exercise on mitochondrial biogenesis regulators, Nrf2 anti-oxidant signaling pathway and muscle damage levels were investigated. Materials and Methods: Balb/c male mice were divided into six experimental groups: control, control+CrM, high-intensity exercise, high-intensity exercise+CrM, low-intensity exercise, and low-intensity exercise+CrM. Mice were given CrM supplementation and at the same time, low and high-intensity exercise was applied to the groups on the treadmill at 30min/5day/8week. Then, mitochondrial biogenesis marker (PGC-1α, NRF-1, TFAM), Nrf2 and HO-1 protein expressions, total oxidant-anti-oxidant status level, and histopathological changes were investigated in serum and muscle tissue. Results: Exercise intensity and CrM supplementation were found to be effective factors in mitochondrial biogenesis induction via the PGC-1α signaling pathway. Nrf2 and HO-1 protein levels increased with exercise intensity, and this result was directly related to serum oxidative stress markers. In addition, CrM supplementation was effective in reducing exercise-induced muscle damage. Conclusion: This combination induced skeletal muscle adaptations, including mitochondrial biogenesis and enhanced anti-oxidant reserves. This synergistic effect of dietary supplementation with low-intensity exercise may be valuable as a complement to treatment, especially in diseases caused by mitochondrial dysfunction.